Water-based paint formulations - Flick, Ernest W. (Noyes Data Corp., 1975)
This collection of 232 water-based trade and industrial formulations will be of value to technical and managerial personnel in paint manufacturing companies and firms which supply raw materials or services to these companies, and to those interested in less hazardous, environmentally safer formulations. The book will be useful to both those with extensive experience as well as those new to the field. This book includes new and different formulations than those included in the previous volumes. The data consist of selections of manufacturers' suggested formulations made at no cost to, nor influence from, the makers or distributors of these materials. The information given is presented as supplied; the manufacturer should be contacted if there are any questions. Only the most recent data supplied us has been included. Any solvent contained is minimal. The table of contents is organized in such a way as to serve as a subject index. The formulations described are divided into sections which cover exterior, interior, and exterior and/or interior water-based paints, enamels, and coatings, as indicated below. Included in the descriptive information for each formulations, where available, the following properties may be listed: viscosity, solids, content, % nonvolatiles, pigment volume concentration, density, pH, spatter, leveling, sag resistance, scrub stability, freeze-thaw stability, ease of application, gloss foaming, cratering, brightness, opacity, water spotting, adhesion to chalk, brush cleanup, reflectance, and sheen.